Prospects of using nanopowders as flame retardant additives; Advanced Materials Research; Vol. 872 - Nazarenko O. B. Olga Bronislavovna; Amelkovich Yu. A. Yuliya Alexandrovna; Ilyin A. P. Aleksandr Petrovich; Sechin A. I. Aleksandr Ivanovich (2014, 2014)
Title screen